GE_GERICHTE P/3426/2019 vom 23. Juni 2020 - GE Cour de justice (2020)
PORNOGRAPHIE DURE;SÉJOUR ILLÉGAL;IN DUBIO PRO REO;ERREUR DE DROIT(DROIT PÉNAL);DÉLIT CONTINU;PEINE MAXIMALE;DIRECTIVE 2008/115/CE;EXPULSION(DROIT PÉNAL) | CP.197.al4; CP.66a; CP.66abis; LEI.115.al1.letb; CP.21